1 Ω and 10 kΩ high precision transportable setup to calibrate multifunction electrical instruments. (March 2016) - Capra, P.P.; Galliana, F.
Abstract: A temperature controlled 1 Ω and 10 kΩ transportable setup was developed at National Institute of Metrological Research (INRIM) for the calibration and adjustment of multifunction electrical instruments as digital multimeters (DMMs) and multifunction calibrators (MFCs). The two standards are made of two 10 Ω and 100 kΩ resistor nets connected in parallel and inserted in a temperature controlled aluminum structure. Novelties of the realization are the oil insertion of the 1 Ω net with the internal side of the connectors lowering the thermo-electromotive forces (EMFs) effects, and the possibility to know instantly the temperatures of the environment, of the internal of the structure and the last calibration values of the 1 Ω and10 kΩ standards. Short- and mid-term stabilities of the setup standards resulted on the order and in some cases better than other metrology-grade 1 Ω and 10 kΩ commercial items. The transport of the setup even turning off its temperature control did not cause appreciable measurement variations on the two standards. The standards uncertainties meet those requested by DMMs and MFCs manufacturers to calibrate and adjust these instruments. A test to adjust a MFC gave satisfactory results.